Proyecto arroz CIAT/Cirad: mejoramiento genético de arroz para América Latina y el Caribe - Grenier, Cécile; Ospina, Yolima (International Center for Tropical Agriculture, 2011)
The International Center for Tropical Agriculture (CIAT) and the French agricultural research center for international development (Cirad) have worked together since 1992 on a project for the genetic improvement of upland rice for Latin American and the Caribbean (LAC). The goal is to develop and enhance populations that would become sources of new genetic material; lines and progenitors, carrying the specific traits required by the region’s national programs. The strategy has been to create synthetic populations with broad genetic diversity, to evaluate them for specific traits of interest, to select and recombine the best units, and to pursue this recurrent selection (RS) scheme for further genetic enhancement. Through this improvement strategy, new varieties have been developed that are now released in different countries of LAC.